Уменьшение систематической погрешности емкостного датчика биений вала за счет изменения формы активного электрода - Левицкий, А.С.; Новик, А.И. (Технічна електродинаміка, 2011)
Capacitive sensor of radical shaft beats of huge electric machines which has an active scalene rectangle electrode has been suggested. While measuring a shorter side of rectangle arranges perpendicular to longitudinal axis of shaft. The calculation of sensor transfer function has been carried out. Analysis of the error caused by curvature of target cylindrical surface has been performed. Also, it has been shown that the error depends only on the side dimension of active electrode which is perpendicular to longitudinal axis of shaft. Comparison of the error with the capacitive sensor error of shaft beats with an active rounded electrode having the same area has been made. Also, it has been shown that the error of sensor with rectangular electrode is several times smaller.